Finite Element Simulation of Jet Combustor Using Local Extinction Approach with in Eddy Dissipation Concept - Ghasemi, E.; Soleimani, Soheil; Almas, M.A. (Journal of Advanced Thermal Science Research, 2015)
Non-premixed turbulent reacting flow in a methane-fuelled coaxial jet combustor has been studied numerically employing Reynolds Averaged Navier-Stokes (RANS) models. A Finite Element Method (FEM) based solver and Eddy Dissipation Concept (EDC) is used to simulate the methane air reaction inside the combustor. Simulations were carried out using the k-w (k-omega) turbulence model to handle the fluid flow simulation along with heat transfer and chemical reaction. The results were compared to available LES numerical results and experimental data for predicting velocity, and temperature fields. Velocity, temperature and concentration of the different species are also plotted at different cross sections of the methane burner.